1972
DOI: 10.1038/bjc.1972.43
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Lymphocytic Infiltration in Neuroblastoma

Abstract: Summary.-A study of the significance of lymphocytic infiltration was made in a retrospective series of 23 primary neuroblastomata. The degree of lymphocytic infiltration was estimated and scored in 5 categories. Non-parametric rank order statistical methods were used to establish quantitative correlations, particularly with the duration of survival. A significant positive correlation was found both in infancy and childhood. It was found, unexpectedly, that the presence of metastases did not invalidate the corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

1973
1973
1982
1982

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(41 citation statements)
references
References 27 publications
1
40
0
Order By: Relevance
“…Similarly, antigens associated with transformation to the malignant state may be expressed (Laurence and Neville, 1972) and choriocarcinoma is neither more nor less likely than other tumours to have such antigens. It is interesting that similar cellular infiltrates to those seen in choriocarcinoma have also been described in other tumours, for example, in carcinoma of the stomach (Black, Opler and Speer, 1954), carcinoma of the breast (Berg, 1962;Black, Opler and Speer, 1956;Hamlin, 1968), malignant melanoma (Cochran, 1969) and neuroblastoma (Lauder and Aherne, 1972). Thirdly, since choriocarcinoma is a malignant allograft (Dowling, 1957;Hirsch, 1962) it may also exhibit individual-specific or transplantation antigens, inherited from the male parent of the antecedent conception.…”
Section: Discussionmentioning
confidence: 71%
“…Similarly, antigens associated with transformation to the malignant state may be expressed (Laurence and Neville, 1972) and choriocarcinoma is neither more nor less likely than other tumours to have such antigens. It is interesting that similar cellular infiltrates to those seen in choriocarcinoma have also been described in other tumours, for example, in carcinoma of the stomach (Black, Opler and Speer, 1954), carcinoma of the breast (Berg, 1962;Black, Opler and Speer, 1956;Hamlin, 1968), malignant melanoma (Cochran, 1969) and neuroblastoma (Lauder and Aherne, 1972). Thirdly, since choriocarcinoma is a malignant allograft (Dowling, 1957;Hirsch, 1962) it may also exhibit individual-specific or transplantation antigens, inherited from the male parent of the antecedent conception.…”
Section: Discussionmentioning
confidence: 71%
“…The presence in some tumours of large numbers of lymphocytes has alreadv been mentioned and has been demonstrated by several groups of workers (Black et al, 1956;Berg, 1959;Lauder and Aherne, 1972). In the gastrointestinal tract lymphocyte infiltration may also reflect nonspecific factors such as ulceration and infection.…”
Section: Disc1ussionmentioning
confidence: 88%
“…Several studies have demonstrated that in a varietv of malignant neoplasms lvmphocytic infiltration of the tumour is associated with longer survival (Black, Opler and Speer, 1.956;Berg. 1959;Lauder and Aherne. 1972).…”
Section: Disc1ussionmentioning
confidence: 99%
“…gastric cancer (Black et al 1954(Black et al , 1956(Black et al , 1971Cutler et al 1969), choriocarcinoma (Elston 1969), cutaneous malignant melanoma (Thompson 1972), neuroblastoma (Lauder and Aherne 1972), cervix carcinoma (Hamazaki 1968), esophageal carcinoma (Takahashi 1961) and pharyngeal carcinoma (Bennett et al 1971). Therefore, lymphocytic reaction in or around the tumor has been of great interest for patho logists.…”
mentioning
confidence: 99%